A study of the relationship between physical fitness, physical and psychological development and their impact on the level of special training among seven-year-old hockey players - Abramova, T. F.; Nikitina, T. M.; Balabokhina, T. V.; Shachnev, E. N. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the relationship between indicators of physical fitness, physical and psychological development and manifestations of special fitness in hockey players aged seven.